2018
DOI: 10.15252/emmm.201708550
|View full text |Cite
|
Sign up to set email alerts
|

LETM 1 couples mitochondrial DNA metabolism and nutrient preference

Abstract: The diverse clinical phenotypes of Wolf–Hirschhorn syndrome (WHS) are the result of haploinsufficiency of several genes, one of which, LETM1, encodes a protein of the mitochondrial inner membrane of uncertain function. Here, we show that LETM1 is associated with mitochondrial ribosomes, is required for mitochondrial DNA distribution and expression, and regulates the activity of an ancillary metabolic enzyme, pyruvate dehydrogenase. LETM1 deficiency in WHS alters mitochondrial morphology and DNA organization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…They also found that those phenotypes segregated with seizures in their WHS cohort. A recent work by Durigon et al () seemed to support these findings.…”
Section: Introduction: Wolf‐hirschhorn Syndromementioning
confidence: 75%
“…They also found that those phenotypes segregated with seizures in their WHS cohort. A recent work by Durigon et al () seemed to support these findings.…”
Section: Introduction: Wolf‐hirschhorn Syndromementioning
confidence: 75%
“…6,8 ATAD3 also co-purifies with the mitochondrial protein synthesis machinery, mtDNA, and mitochondrial cholesterol, 7,8,20 and there is evidence that the mitochondrial nucleoprotein complexes are interlinked. 21,22 Hence perturbed cholesterol-containing micro-domains could be the common factor linking all the features associated with ATAD3 deficiency.…”
mentioning
confidence: 99%
“…Very recently researchers have recognized an important role for LETM1 in mitochondrial ribosome function. Moreover, fibroblasts from WHS patients displayed clear abnormalities in mitochondrial morphology, mtDNA organization and a remodeling of oxidative metabolism (Durigon et al, ). The emerging importance of LETM1 in mitochondrial morphology maintenance and function, suggests a possible role of the p.Arg294Gln variant in the determination or worsening of at least a portion of our patient's symptoms, and may contribute to the severe mitochondrial dysfunction revealed by studies on muscle biopsy of our proband.…”
Section: Discussionmentioning
confidence: 99%